Discussion over Dawkins - Doleček, Pavel (Teorie vědy / Theory of Science, 2011)
The study reviews following books: Richard DAWKINS, Boží blud: Přináší náboženství útěchu, nebo bolest? Praha: Academia 2009, 480 s. (The God Delusion, translated by Zuzana Gabrová with epilogue by Filip Jaroš and Stanislav Komárek); HANUŠ, J. - VYBÍRAL, J. (eds.), Dawkins pod mikroskopem: Diskuse nad knihou Richarda Dawkinse Boží blud. Brno: Centrum pro studium demokracie a kultury 2010. The aim of this study is to overview the debate inspired by publication of the Czech translation of Dawkins’ book The God Delusion, whose most complex contributions inspired publication of the book Dawkins pod mikroskopem.